SYNTHESIS OF GLYCEROL CARBONATE AND KINETIC STUDY OF UREA GLYCEROLYSIS REACTION USING Zn(sec-BUTOXIDE) 2 - Dwi Andriyani, Dita
G vcero/ carbonate is one of value-added chemicu/.r; from glycerol. It has wzde applications, such as monomer for polycarbonate, surfactant , electrolytes, and alternative organic solvents. One of the promising route for glycerol carbonate :,ynthesis is urea glycerolysis. The route does not need solvent , and the co-product (NH3) may be cycledfor urea manufacture. The urea is also a readily available source. The reaction was initiated by catalyst to produce glycerol carbonate in a high yield and selectivity. Many researchs explore effective catalysts for such a reaction. One of the rarely explored caral_vst is Zn-alkoxy. The(irst Zn- alkoxy explored in the reaction was Zinc(monoglycerolate) (ZMG) . The reaction took place in 7 h and 5mol% catvast. The synthesis of ZMG was also a multi step reactwn. Therefore, exploration of a simple Zn(alkoxide) is interesting to be done. This research aims to study the .<.ynthesis of glycerol carbonate from Zn-cataly::ed urea glycerolysis. The Zn catalyst was prepared from the reaction between ZnCh and Al(OC.JH9h in dry THF Zn-alkoxide formation was observed from the Zn-0 alkoxy vibration at 902-910 em -1 Five parameters, i. e.. temperature, reaction time. catalyst concentration, and solvent were evaluated to seek an optimum reaction condition. The glycerol carbonate formatiOn was observedfrom the carbonyl cyclic